Analisis Faktor Dominan Penyebab Terjadinya Pembengkakan Biaya (Cost Overrun) pada Proyek Konstruksi Gedung Pemerintah Kategori Kecil di Kota Pekanbaru - Rian Tri Komara Iriana; Mardani Sebayang; Muhammad Rilly Aka Yogi (Jurnal Teknologi dan Rekayasa Sipil, 2022)
In organizing building construction especially in Pekanbaru, cost factor is a mainly considered factor due to its relation with the great number of investment for owner. Therefore, project`s cost needs to be well-managed in order to minimalize the possibility of overrun cost. The purpose of this research was to discover the rate of validation, and to analyze the most dominant factor which has triggered the overrun cost case on small categorized government building construction project in Pekanbaru. Data collection was thoroughly done by deploying questioners to small contractors in the city of Pekanbaru. The number of samples in this research was 14 respondents. The profile of those respondents were grouped according to their gender, age, position in occupation, experience, and education background. The collected data were analyzed by using validation and reliability test, factor analysis, classic assumption test, and multiple linear regression. The data processing was done by using SPSS software (Statistical Product and Service Solution) version 24. As a result, it was obtained that the most dominant factor which has triggered the overrun cost case on small categorized government building construction project in Pekanbaru consisted of: planning and construction department i.e. handling too many projects at the same time with the percentage of 92,0%, resource coordination department i.e. lack of labours with the percentage of 86%, control department i.e. payment delays with the percentage of 63,2%